Resurrecting Nannie Minor and Orie Hatcher: Emergence of Professional Social Work Education in One Southern City. (May 2015) - Netting, F. Ellen; O'Connor, Mary Katherine; Fauri, David P.; Coles, D. Crystal; Prorock-Ernest, Amy
In this article, we raise two feminists (Minor and Hatcher) from erasure by recognizing the importance of their roles in the development of professional social work education. First, we tell a story of how emerging semiprofessions were intertwined, only to become separate over time. Next we focus on the influence of two feminists who came from other semiprofessions than social work and were instrumental in cocreating a School of Social Work. Minor and Hatcher's erasure in the formal histories of the School demonstrates the gendered nature of the professional education process.